DEMOCRATIC EDUCATION THROUGH HISTORY LEARNING USING SOCIAL HISTORY TEACHING MATERIALS - Kurniawan, Hendra (International Journal of Indonesian Education and Teaching (IJIET), 2017)
The democracy practice could grow when the nation’s generation had history awareness and be a good citizen. So the democratic education should be developed, one of the ways was through history learning in schools. Social history teaching materials, especially regarding women and ethnic was full of democratic values, there were freedom and egalitarian. Various experiences and problems of democracy could not be separated from society life since ancient era. By understanding the social dynamics through history learning, the young generation was expected to be wise in determining the democracy continuity for nation’s future.DOI: https://doi.org/10.24071/ijiet.2017.010205